The gaps in fatwa on intersex corrective surgery: Some reflections in the context of Malaysia - Mohd Badrol, Muhammad Afif; Awang, Abdul Bari; Haneef, Sayed Sikandar Shah; Zainuddin, Ani Amelia (IIUM Press, 2018)
Intersex being a birth impairment in human babies is a fact of human precreation. Opposed to normal birth of humans as males and females incidents of babies with vague gender identity have perturbed people and families as to how to socially place them within the binary system of men and women in the community. In Islam, it is more important in view of the gendered orientation of some Islamic laws and its system of social ethics. Accordingly, jurists formulated an Islamic blueprint to manage this segment. However, their main criteria to align such individuals to one of the normal genders were inadequate to assign a specific sex to all intersex. Medical science, on the other hand, proposes not only to achieve precise diagnoses of intersex conditions but also to manage them medically. Accordingly, Muslim jurists and muftis by and large celebrated this medical solution as a better remedy to resolve this juridical perplexing question. This study, however, argues that juristic stamp of approval needs to be more ethically grounded so as to avoid pitfalls inherent in this medical innovation.